Commercial Policy Uncertainty, the Expected Cost of Protection, and Market Access - Joseph F. Francois; Will Martin (Tinbergen Institute, 1998)
Protection unconstrained by rules often varies substantially over time. Rules-based disciplines likeOECD industrial tariff bindings negotiated under GATT since 1947 and new Uruguay Roundbindings on agricultural and services trade and on developing country industrial tariffs, constrain thisvariability. We examine the theoretical effects of such constraints on the expected cost of protectionand offer a formalization of the concept of market access, emphasizing both the first and secondmoments of the distribution of protection. As an illustration, we provide a stylized examination ofUruguay Round agricultural bindings.
Keywords: 330; Protektionismus; Zoll; Theorie